'Primary gingival and later primary vulval carcinomas arising in lichen planus: report of a case and clinical suggestions for diagnosis of a neglected disease'. (2nd November 2019) - Basile, Stefano; Pinelli, Sara; Bottone, Pietro; Artini, Paolo Giovanni; Plotti, Francesco; Panici, Pierluigi Benedetti
Abstract: Lichen planus (LP) is a chronic immune-mediated dermatosis mainly affecting skin, oral, and genital mucosa. The heterogeneous clinical presentation, spectrum of symptoms depending on subtype and overlap with other vulval and cutaneous disorders can lead to challenging in diagnosis. We report an unusual case of vulval SCC arising within a patient with initial oral mucosal lichen planus who later developed lichen planus of the vulva. Discussion of this case is important as it typifies the difficulties in diagnosis of vulvo-vaginal disorders and potential complications. Evidence is available that lichen planus may be potentially precancerous condition and is associated with SCC development. This case may confirm an inherent oncologic potential of the disease. All efforts must be made by specialists involved in the management of this disease to obtain an early diagnosis, ensure proper treatment and adequate follow up. This highlights the need to perform vulval examination in patients with symptoms or with a history muco-cutaneous LP and if necessary consider referral to specialist center for biopsy and management.